2012
DOI: 10.1155/2012/804717
|View full text |Cite
|
Sign up to set email alerts
|

Adrenomedullin as a Growth and Cell Fate Regulatory Factor for Adult Neural Stem Cells

Abstract: The use of stem cells as a strategy for tissue repair and regeneration is one of the biomedical research areas that has attracted more interest in the past few years. Despite the classic belief that the central nervous system (CNS) was immutable, now it is well known that cell turnover occurs in the mature CNS. Postnatal neurogenesis is subjected to tight regulation by many growth factors, cell signals, and transcription factors. An emerging molecule involved in this process is adrenomedullin (AM). AM, a 52-am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 173 publications
(240 reference statements)
1
8
0
Order By: Relevance
“…Pio et al [163] demonstrated that AM in milk has a growth-promoting activity on an intestinal cell line (Int-407) because an anti-AM antibody partially blocks the milk-induced growth. This is in line with several studies that have proven that AM acts as an autocrine/paracrine growth factor in other cell types [58,[164][165][166].…”
Section: Adrenomedullin Actions In the Intestinesupporting
confidence: 91%
“…Pio et al [163] demonstrated that AM in milk has a growth-promoting activity on an intestinal cell line (Int-407) because an anti-AM antibody partially blocks the milk-induced growth. This is in line with several studies that have proven that AM acts as an autocrine/paracrine growth factor in other cell types [58,[164][165][166].…”
Section: Adrenomedullin Actions In the Intestinesupporting
confidence: 91%
“…AM exerts various actions on the vasculature, such as vasodilation, angiogenesis, and regulation of blood brain barrier. Similarly, AM acts as a neurotransmitter, neuromodulator, or neurohormone [18]. In addition, AM can be considered as a therapeutic target for CNS diseases since several animal studies have demonstrated that AM reduces neuronal injuries [3235].…”
Section: Discussionmentioning
confidence: 99%
“…AM has diverse biological actions, including cell proliferation and differentiation in a paracrine and autocrine manner [1720]. AM also have important roles for cellular function of immature cells, such as endothelial progenitor cell (EPC), mesenchymal stem cell, hematopoietic stem cell, adrenocortical stem cell, and neural stem/progenitor cell (NSPC) [18, 21, 22]. Recently, it has been reported that AM may also regulate white matter function in the brain.…”
Section: Introductionmentioning
confidence: 99%
“…Adrenomedullin receptors are widely distributed in the brain and AM is reported to act as a neurohormone and neurotransmitter [ 14 ]. Literature has also suggested that neuronal injury can be protected by activating the AM receptor, and thereby effectively aiding in the management of certain CNS disorders [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%